Effect of combined guided imagery and lavender aromatherapy on anxiety levels among twelfth-grade students - Lisa Nurul; Lailatul Fadilah; Osep Yasier Almunsiri; Alif Nurul Rosyidah (JOURNAL OF Mental Health Concerns, 2026)
Background: Adolescence is a transitional period characterized by physical, psychological, and social changes that can increase the risk of anxiety. Uncontrolled anxiety can affect mental health, learning concentration, and adolescents' ability to adapt. Guided imagery and lavender aromatherapy are non-pharmacological therapies that can provide a relaxing effect, thus helping to reduce anxiety levels. Purpose: To determine the effect of the combination of guided imagery and lavender aromatherapy on the anxiety levels of twelfth-grade students. Method: A pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 36 respondents selected using purposive sampling. Anxiety levels were assessed using a teenage anxiety questionnaire Data were analysed using univariate and bivariate analysis with a paired t-test. Results: Based on the research results, the average anxiety level before the intervention was 30.83 ± 2.823 and decreased to 17.25 ± 3.467 after the intervention. The Paired T-Test results showed a p-value < 0.001, indicating that there is an effect of the combination of guided imagery and lavender aromatherapy on anxiety levels in adolescents. Conclusion: The combination of guided imagery and lavender aromatherapy is effective in reducing anxiety levels in twelfth-grade students.Keywords: Adolescents; Anxiety; Guided Imagery; Lavender Aromatherapy.